PEMANFAATAN TEMPURUNG KELAPA DI DESA BAWOFANAYAMA - Telaumbanu, Tatema; Fatolosa Hulu; Lies Dian Marsa Ndraha; Murnihati Sarumaha; Baziduhu Laia; Kaminudin Telaumbanua (Haga : Jurnal Pengabdian Kepada Masyarakat, 2024)
Coconut shell is an organic waste that comes from processed coconuts which is obtained after taking the coconut meat to make coconut milk and so on. Coconut shells have many benefits for humans if they can be used creatively. The aim of this service is to find out the process of utilizing organic waste, especially coconut shells in Bawofanayama Village, Fanayama District, South Nias Regency. Based on the results of this research, the process of processing coconut shells to make charcoal is carried out in stages, namely; cleaning, drying, providing containers for burning, burning, collecting charcoal and distributing or selling. Based on these results, it is clearly visible and proven that natural waste or waste, especially coconut shells originating from human activities, can be reused as income. So this can improve human quality creatively and economically. Therefore, it is hoped that the community can utilize organic waste, especially coconut shell waste, to increase the economic value of the community itself.